AIDS mortality trends in Mexico, 1988-1997 - Hernández-Girón Carlos; Tovar-Guzmán Víctor; del Río Carlos (Instituto Nacional de Salud Pública, 2002)
Objective. To assess the geographic distribution and trends of AIDS deaths for the 1988-1997 period in Mexico. Material and Methods. Crude and adjusted mortality rates were estimated for the 1988-1997 period. A trend test was performed using the simple linear regression method. Standardized mortality ratios (SMR) and years of potential life lost (YPLL) were calculated for each Mexican state. Results. During the study period (1988-1997), there were 26,999 AIDS deaths in Mexico; 86.5% (23,354) of them were among men. The mean age at the time of death was 38.4 years for men and 37.7 years for women (p> 0.05). The crude AIDS mortality rate for the period of study was 3.02 cases (95% CI: 2.94, 3.06) per 100,000 inhabitants. The adjusted rate was 3.13 (95% CI: 3.09, 3.17), with 5.22 (95% CI: 5.16 - 5.29) for men and 0.82 (95% CI: 0.79-0.84) for women. The states with the highest SMR were: Baja California (SMR: 248.69; 95% CI: 234.02-263.36), Mexico City (SMR: 220.74; 95% CI: 215.57-225.91), and Jalisco (SMR: 169.16; 95% CI: 162.88-175.44). Similarly, a Potential Lost Life Years Index (PLLYI) analysis by state showed a greater risk of premature AIDS mortality in the same states [Baja California (PLLYI index: 236.33; 95% CI: 233.97-238.68), Mexico City (PLLYI: 194.68; 95% CI: 193.88 - 195.48), and Jalisco (PLLYI: 170.69; 95% CI: 169.60-171.79)]. Conclusions. Mortality trends indicate that AIDS mortality in Mexico increased by an annual rate of 23% between 1988 and 1997. The adjusted AIDS mortality rate increased from 0.75 per 100 000 in 1988, to 4.20 per 100 000 in 1997, with the largest burden of mortality in men (male to female ratio of 6:1). We therefore expect that a decreasing effect on AIDS mortality trends will be observed in the next years.